High fidelity - Hornby, Nick. (London : Indigo, 1996)
The romantic trials of the owner of a London record shop, after his girlfriend leaves him for another man.
Keywords: Popular music fans -- England -- Fiction; Man-woman relationships -- Fiction; Young men -- England -- Fiction